MULTIAGENT COLLABORATIVE COMPUTATION FOR AIRCRAFT MAINTENANCE SYSTEM - Sumari, Arwin Datumaya Wahyudi; Ahmad, Adang Suwandi (Sekolah Tinggi Teknologi Adisutjipto, 2017)
Quick-and-accurate decision is a primary requirement for achieving a mission’s successfulness in many organizations whether they are militaries or civilians. The larger and more complex the scope of a mission the longer the time will be needed to perform decision-making. A complex mission such as retaining a sustainable mission of aircrafts deployed in certain remote bases will require a 24-hour of standby on-site or off-site maintenance teams. The most common problem arisen from humans in such situations is the fatigue that can occur anytime to any of them during a continuing mission and of course, it can affect the continuity of the mission and delay or disappoint the mission achievement. In this paper we address the concept of the utilization of Multiagent Collaborative Computation (MCC) paradigm in supporting the decision-making process in aircrafts maintenance during a sustainable mission in remote bases. The ultimate goal of the MCC-based aircraft maintenance system is comprehensive information regarding the maintenance procedures in order to keep the aircrafts serviceable during the mission implementation. In this paper we also present the technique to obtain the comprehensive information as the basis for decision-making called A3S (Arwin-Adang-Aciek-Sembiring) information-inferencing fusion method